"Preparation and application of under water low frequency sound-absorbing rubber material" - XIAO Cheng-yuan, TAN Lian-ying, MU Hong-shuai, LIU Quan, XIE Jing-hui (Hecheng xiangjiao gongye)
A kind of low frequency sound-absorbing rubber material under water for sea chest was prepared using nitrile rubber with high bound acrylonitrile content as matrix, the effects of different fillers and damping agents amount on its elastic modulus, loss factor, and mechanical properties were investigated, and sound-absorbing panel products were trial produced based on this. The results showed that a synergistic effect could be formed by combining 100 mesh hollow structure vermiculite and silicate microspheres in a 10/10 (mass ratio, the same below). The filled sound-absorbing rubber had relatively low elastic modulus, high loss factor, and good interlayer adhesion performance. The sound-absorbing rubber had better interlayer bonding performance, relatively lower elastic modulus, and higher loss factor when the lamellar structure of Qianwei powder and mica was used in ratio of 7/14. Hindered phenol antioxidant AO-80 could effectively improve the loss factor of the sound-absorbing rubber, and its amount should be 10 phr (by mass). The sound-absorbing panel product, which used a combination of vermiculite and silicate microspheres, as well as a combination of Qiangwei powder and mica as the main sound-absorbing fillers, and AO-80 as damper, had an average sound-absorption coefficient greater than 0.7 at frequencies of 1-4 kHz.